PERSEPSI GURU TENTANG GAYA KEPEMIMPINAN KEPALA SEKOLAH DI SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI KABUPATEN SIJUNJUNG - Neni Marlina (Jurnal Bahana Manajemen Pendidikan, 2013)
The background research is phenomenon indicating implementation of headmaster hasnt applying force leadership good to a teacher at the school. Research is intended to gain information about teacher perception against the style of leadership headmaster district SMKN Kabupaten Sijunjung in improving the performance of duties teacher on the style of leadership that is task oriented on an errand and the styles of leadership that is releations oriented toward inferiors. The population was 144 teacher PNS of SMKN Kabupaten Sijunjung. Samples taken are 39% of the total population is 65 people.. Instrument used in this research was the questioners which has been tasted for its validity and reliability.. In general, the perception of teachers on the implementation leadership style functions headmaster of SMKN Kabupaten Sijunjung in the category of quite good length with an average score overall was 3.59 with the level of achievement 71.9 %. Kata kunci: leadership style